Summary Proceedings: of the Fifty-Fourth Annual Meeting of the Board of Governors September 28-30, 1999 - International Monetary Fund; The World Bank (Washington D.C., 1999)
These contains the summary proceedings include statements, or portions of statements, relating to the work of the Fifty-Fourth Annual Meeting of the Board of Governors of the International Monetary Fund, held in Washington, D.C., from September 28-30, 1999.
usc 27/08/2021
Ref.